2022
DOI: 10.1596/1813-9450-10113
|View full text |Cite
|
Sign up to set email alerts
|

Women's Political Representation and Intimate Partner Violence

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
2
3
0
Order By: Relevance
“…On the one hand, a more active role of women in the political public sphere may lead to more tensions and disputes in private life, specifically in the context of intimate relationships. This causal effect has been previously found in India [45]. On the other hand, since physical violence is one of the most visible faces of IPV, more concerns about this issue are observed in municipalities in which women and girls have greater probabilities of being victimized.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…On the one hand, a more active role of women in the political public sphere may lead to more tensions and disputes in private life, specifically in the context of intimate relationships. This causal effect has been previously found in India [45]. On the other hand, since physical violence is one of the most visible faces of IPV, more concerns about this issue are observed in municipalities in which women and girls have greater probabilities of being victimized.…”
Section: Discussionsupporting
confidence: 67%
“…In a study analyzing data from Samoa, it was found that, in addition to individual-and relationship-level factors, community characteristics, such as greater proportion of women engaged in household decision-making, as well as higher rates of employed men, were associated with lower levels of IPV [44]. Similarly, data from India indicate that the level of political involvement among women at the community level correlates significantly with marital conflicts and instances of violence, the overarching observation of this study was that increased representation of women in political spheres at the district level is associated with higher risks of physical IPV experienced by women [45]. Community dissimilarities in urbanization and education were identified as contributing factors to the likelihood of experiencing IPV in Ethiopia [19].…”
Section: Community-level Factorssupporting
confidence: 55%
“…To mirror the work of Anukriti et al (2022), we also test for changes in the number of children a woman has ever given birth, with an average in the sample of approximately 4.5. It is worth noting that these women are of child-bearing age (15-49) and may have more children in the future.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
“…It is worth noting that these women are of child-bearing age (15-49) and may have more children in the future. Anukriti et al (2022) suggest that con ict arises as women increase their use of contraceptives and lower their fertility when governments are more favorable to women.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
See 1 more Smart Citation